A New Paradigm in Chronic Bladder Pain. (1st December 2014) - Wesselmann, Ursula
ABSTRACT The concept of visceral pain has moved from organ-centered disease to a conceptualization based on pathophysiological mechanisms, integrating psychosocial and sexual dimensions. The terms painful bladder syndrome and bladder pain syndrome have been coined to include all patients with bladder pain. There is substantial overlap between IC/BPS and other pelvic/abdominal pain syndromes IC/BPS is likely to be underdiagnosed and undertreated in both men and women IC/BPS requires a multidisciplinary team approach toward management. This report is adapted from paineurope 2014; Issue 2, ©Haymarket Medical Publications Ltd, and is presented with permission. Paineurope is provided as a service to pain management by Mundipharma International, LTD and is distributed free of charge to healthcare professionals in Europe. Archival issues can be accessed via the website: http://www.paineurope.com at which European health professionals can register online to receive copies of the quarterly publication.